Significance of Disability Inclusive Public Transport in Trujillo, Perú - Rojas , Karin Ponce (Science and Technology - Recent Updates and Future Prospects Vol. 3, 2024)
Aims: The objective of this research is to determine the relationship between the management of inclusive urban public transport and the accessibility of persons with disabilities in the city of Trujillo, 2020, and how public management impacts this group of citizens. Background: Accessible transport is a key factor in access to essential urban resources and services, including housing, employment, social welfare, and recreation. It is important to be inclusive of the needs of individuals with disabilities in the design of the built environment, urban facilities and services, to enhance the quality of life for all, and thus support community integration. Methodology: The study was carried out in the city of Trujillo, Peru in 2020. A questionnaire was used based on the dimensions of each variable. The variables were: Inclusive urban public transport management composed of 5 dimensions (equipment and services, adapted vehicles, preferential rate, regulatory compliance, state of the roads) and accessibility of people with disabilities, composed of 5 dimensions (physical environment, attitudinal, social activities, mobility, comfort). Spearman's rank correlation was used. Results: The results allowed us to identify that the management of inclusive urban public transport in the city of Trujillo has a predominantly deficient level, and accessibility for people with disabilities is mostly deficient. It was carried out in the city of Trujillo, Peru in 2020 with a sample population of 196 people. Implying access to mass urban transport systems for individuals with physical and hearing disabilities is an essential right among the various goods, services and products, which should be conceived or have accessibility to reduce the discriminatory levels existing in the disabled citizens. Conclusion: The accessibility of people with disabilities in the city of Trujillo was found to be directly and significantly correlated with the management of inclusive urban public transportation and its components (equipment and services, adapted vehicles, preferential rates, regulatory compliance, state of the roads).